RACK1A positively regulates opening of the apical hook in Arabidopsis thaliana via suppression of its auxin response gradient - Ma, Qian; Liu, Sijia; Doyle, Siamsa M; Raggi, Sara; Pařízková, Barbora; Barange, Deepak Kumar; Ratnakaram, Hemamshu; Wilkinson, Edward G; Crespo Garcia, Isidro; Bygdell, Joakim; Wingsle, Gunnar; Boer, Dirk Roeland; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2025)
Apical hook development is an ideal model for studying differential growth in plants and is controlled by complex phytohormonal crosstalk, with auxin being the major player. Here, we identified a bioactive small molecule that decelerates apical hook opening in Arabidopsis thaliana. Our genetic studies suggest that this molecule enhances or maintains the auxin maximum found in the inner hook side and requires certain auxin signaling components to modulate apical hook opening. Using biochemical approaches, we then revealed the WD40 repeat scaffold protein RECEPTOR FOR ACTIVATED C KINASE 1A (RACK1A) as a direct target of this compound. We present data in support of RACK1A playing a positive role in apical hook opening by activating specific auxin signaling mechanisms and negatively regulating the differential auxin response gradient across the hook, thereby adjusting differential cell growth, an essential process for organ structure and function in plants.
Keywords: apical hook; proteiny huseníčku; regulace genové exprese u rostlin; Receptors for Activated C Kinase; Arabidopsis; Indoleacetic Acids; auxin; regulátory růstu rostlin; Arabidopsis Proteins; receptory pro aktivovanou kinasu C; kyseliny indoloctové; signální transdukce; Gene Expression Regulation, Plant; differential cell growth; Plant Growth Regulators; Signal Transduction